Acute effect of an amino acid mixture in the rat glycemic profile. Issue 8 (14th March 2019) - Pena, Maria J.; Guerreiro, Susana G.; Rocha, Júlio C.; Morais, Tiago; Pereira, Sofia S.; Monteiro, Mariana P.; Borges, Nuno
Abstract: Amino acid mixtures (AAM) are protein substitutes used for phenylketonuria treatment, but their metabolic effects have not been well characterized. The objective of this study was to compare the acute glycemic response to free amino acids (free AA) from AAM with the response to intact protein (iProtein). Male Wistar rats (n = 14) were administered by gavage a bolus of free AA (n = 7) or iProtein as albumin (n = 7) containing equivalent amounts of nitrogen. Blood glucose and insulin levels were measured at baseline and 15, 30, 60 and 120 minutes later, when gut GLP‐1 content and pancreatic insulin, GLP‐1 receptor and Ki67 expression were quantified at 120 minutes time point. After AAM, glucose area under the curve (free AA vs iProtein; P < 0.01), serum insulin levels at 120 minutes (free AA vs iProtein; P < 0.05), colon GLP‐1 content (free AA vs iProtein; P < 0.01), pancreatic GLP‐1 receptor (free AA vs iProtein; P < 0.01) and insulin expression (free AA vs iProtein; p < 0.01) were significantly lower as compared with iProtein. AAM increased Ki67 expression in pancreatic islets (free AA vs iProtein; P < 0.05). In conclusion, this study demonstrated that acute response to AAM differs from iProtein and is characterized by a lower glucose excursion, along with a decrease in gut GLP‐1 and pancreatic GLP‐1 receptor and insulin. This data suggests the modulation of glycemia by free AA is mediated by the incretin axis. Abstract : The data suggests the modulation of glycemia by free amino acids (free AA) is mediated by the incretin axis.